Endothelial Dysfunction in Hypertension: Current Concepts and Clinical Implications - Gallo, Giovanna; Volpe, Massimo; Savoia, Carmine (Frontiers in Medicine, 2022)
Endothelium plays a fundamental role in the cardiovascular system, forming an interface between blood and adjacent tissues by regulating the vascular tone through the synthesis of nitric oxide, prostaglandins and other relaxing factors. Endothelial dysfunction is characterized by vasoconstriction, cell proliferation and shifting toward a proinflammatory and prothrombic state. In hypertension endothelial dysfunction may be involved in the initiation and development of vascular inflammation, vascular remodelling, and atherosclerosis and is independently associated with increased cardiovascular risk. Different conditions such as impaired vascular shear stress, inflammation and oxidative stress, activation of the renin angiotensin system have been described as important pathophysiological mechanisms involved in the development of endothelial dysfunction. The release of extracellular vesicles by neighbouring cells in the vascular wall has emerged as an important regulator of endothelial function and with potential antihypertensive properties and beneficial effects by counteracting the hypertension mediated organ damage. Furthermore, macrovesicles are emerging as an innovative therapeutic approach for vascular protection, allowing the delivery of bioactive molecules, such as miRNA and drugs interacting with the renin angiotensin system. In this review we summarize the available evidence about the pathophysiological implications of endothelial dysfunction in cardiovascular diseases, focusing on hypertension and its sequelae, and the potential innovative therapeutic strategies targeting the endothelium with the aim to improve vascular function and remodeling.